The Subject Dimension of Authorship A New Perspective of Provenance in KO - Tognoli, Natalia; Milani, Suellen Oliveira; Chaves Guimaraes, Jose Augusto [UNESP]; Ernesto de Moraes, Joao Batista [UNESP]; Lykke, M.; Svarre, T.; Skov, M.; MartinezAvila, D. (Ergon-verlag, 2020)
Authorship is a highly thematic and complex element since it brings aspects related to the specificity and context of works' production. Considering that contexts and subjects are dynamic and vary over time and space, this paper aims to present the concept of subject provenance stressing that authorship can be considered as a product of a context - subject historicity, specific themes, and interpersonal networks. The approach taken to identifying essences in this paper is inductive. The discussion highlights that when considering an author as a subject herself/himself and as an access point - from the concept of subject provenance - it is delineated an organic relationship between the authors who participate in the same epistemic community, enriching the representation in the scientific literature. Thus an invisible but strong ribbon that leads to the complete subject context identification ties the author and the content of the document.